Compromiso laboral de los empleados del GAD del cantón Vinces - Santana Luna, Yosselin Kasandra (2018)
The Autonomous Decentralized Government of the canton of Vinces, located between Sucre and Bazar streets belonging to the province of Los Ríos, is a Government enterprise that offers the population a better quality of life, through the equitable administration of resources, which allows carry out the works and services necessary to promote the development of the canton. The Autonomous Decentralized Government of the canton of Vinces has the following municipal offices: Administrative Directorate, Development and Territorial Planning Directorate, Planning and Strategic Management Division, Directorate of Environmental Management and Citizen Security, Directorate of Social Management and Community Development, Municipal Public Works, Directorate of Community Services and Public Spaces, Financial Management, General Coordination, Sindica Procuraduría, General Secretary.